Wideband Metamaterial Absorber Based on Combination of Unit Cells - Puji Handayani; Eko Setijadi; Muhammad Rendy Anggara; Gamantyo Hendrantoro; Ahmad Maulidiyanto (Department of Electrical Engineering ITS and FORTEI, 2020)
Metamaterial absorber is an electromagnetic wave absorber made from metamaterial. It basically works in narrow band frequency as it is designed in a particular shape that related to its resonance frequency. However, some applications, e.g., anechoic chamber, require metamaterial absorber that can work in a wide frequency band. This paper discussed the design of wide band metamaterial absorber using the combination of multiple unit cells. The unit cells type was split ring resonator (SRR). SRR had advantages in terms of its simple shape, it could have more than one resonant frequencies depending on the number of its ring, and its shape could be modified easily to obtain the desired resonant frequencies. We designed metamaterial absorber having good absorbtion rate in 2-10 GHz frequency band. To cover this wide frequency band, we used five unit cells which were arranged on a flat plane. Each unit cell had several resonant frequencies. The design was carried out using simulation software of CST (Computer Simulation System). The fabricated design was measured and the results shown that it had an absorbtion rate of 99% in the measured frequency band.Keywords: absorption rate, metamaterial absorber, unit cell.